Interrelationship of soil microflora and root-knot nematode in roots of tomato - Mayol, Pete (1980)
Necrosis of galled tomato roots was first observed 4, 7 and 10 weeks after the plants were inoculated with 196,000 meloidogyne incognita nematodes and grown in soil with high, medium and low levels microflora, respectively. Necrosis occured, even though the respective galling indices were similar, indicating that microbial densities of a soil, rather than degree of galling have a direct influence on the incidence and severity of root-knot infection. Only the dry foliage weight of plants grown in soil with high microfloral levels and inoculated with nematodes was significantly reduced (P=0.05) by 39% in the 7-week experiment. the reduction was due to premature senescence as a result of root necrosis and to destruction of feeder roots.
Includes bibliographical references (page 77)
Keywords: Agriculture; Tomatoes -- Diseases and pests; Root-knot nematodes -- Effect on tomatoes; Soil microflora -- Effect on tomatoes